Proteomic Study to Survey the CIGB-552 Antitumor Effect. - Rodríguez-Ulloa, Arielis; Gil, Jeovanis; Ramos, Yassel; Hernández-Álvarez, Lilian; Flores, Lisandra; Oliva, Brizaida; García, Dayana; Sánchez-Puente, Aniel; Musacchio-Lasa, Alexis; Fernández-de-Cossio, Jorge; Padrón, Gabriel; López, Luis J. González; et al. (BioMed Research International, 2015)
CIGB-552 is a cell-penetrating peptide that exerts in vitro and in vivo antitumor effect on cancer cells. In the present work, the mechanism involved in such anticancer activity was studied using chemical proteomics and expression-based proteomics in culture cancer cell lines. CIGB-552 interacts with at least 55 proteins, as determined by chemical proteomics. A temporal differential proteomics based on iTRAQ quantification method was performed to identify CIGB-552 modulated proteins. The proteomic profile includes 72 differentially expressed proteins in response to CIGB-552 treatment. Proteins related to cell proliferation and apoptosis were identified by both approaches. In line with previous findings, proteomic data revealed that CIGB-552 triggers the inhibition of NF-κB signaling pathway. Furthermore, proteins related to cell invasion were differentially modulated by CIGB-552 treatment suggesting new potentialities of CIGB-552 as anticancer agent. Overall, the current study contributes to a better understanding of the antitumor action mechanism of CIGB-552.